2021
DOI: 10.1021/acs.inorgchem.1c00389
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ag/AgVO3/N-rGO Hybrid Nanocomposites for Electrochemical Detection of Levofloxacin for Complex Biological Samples Using Screen-Printed Carbon Paste Electrodes

Abstract: Silver vanadate nanorods (β-AgVO3) with silver nanoparticles (Ag-NPs) decorated on the surface of the rods were synthesized by using simple hydrothermal technique and later anchored onto nitrogen-doped reduced graphene oxide (N-rGO) to make a novel nanocomposite. Experimental analyses were carried out to identify the electronic configuration by X-ray diffraction analysis, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy analysis, which revealed monoclinic patterns of the C12/m1 spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…In the previous reports, 56,58,60,61,65 Ag-based electrodes showed excellent redox performance for different species. The oxidation reaction mechanisms of Ag nanoparticles in basic solution were attributed to the generation of the strong oxidant AgO(OH) 2 , 65 whereas their mechanisms for glucose redox in neutral 66–68 and acidic solutions were not clear. 69–71 For the current CNT-NH 2 –Ag/PS paper electrode, the redox reaction of glucose was performed in a neutral solution (Na 2 SO 4 system).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, 56,58,60,61,65 Ag-based electrodes showed excellent redox performance for different species. The oxidation reaction mechanisms of Ag nanoparticles in basic solution were attributed to the generation of the strong oxidant AgO(OH) 2 , 65 whereas their mechanisms for glucose redox in neutral 66–68 and acidic solutions were not clear. 69–71 For the current CNT-NH 2 –Ag/PS paper electrode, the redox reaction of glucose was performed in a neutral solution (Na 2 SO 4 system).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the redox reaction on the CNT-NH 2 -Ag/PS paper electrode was a diffusion-controlled electrochemical process. [62][63][64] whereas their mechanisms for glucose redox in neutral [66][67][68] and acidic solutions were not clear. [69][70][71] For the current CNT-NH 2 -Ag/PS paper electrode, the redox reaction of glucose was performed in a neutral solution (Na 2 SO 4 system).…”
Section: Fabrication and Characterization Of The Cnt-nh 2 -Ag/ps Pape...mentioning
confidence: 99%
“…As an organic combination of carbon electrode and screen-printed electrode, screen-printed carbon electrodes (SPCEs) have unique characteristics including high chemical stability, wide potential window, good biocompatibility, low cost, easy mass production, and disposable use [ 13 , 14 , 15 ]. However, it was proven that VMSF cannot be stably grown on carbon electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with conventional solid electrodes (e.g., glassy carbon electrode-GCE, Au or Pt electrode), screen-printed electrodes (SPEs) have attracted much attention owing to their low cost, easy batch fabrication, convenient array and flexible design, and possibility of low sample consumption [ 10 , 11 , 12 ]. Amongst alternatives, screen-printed carbon electrodes (SPCEs) have great potential in the detection of biomarkers in clinical samples owing to the merits of a wide potential window, low background current, high biocompatibility, and excellent chemical stability [ 13 , 14 , 15 ]. However, modification of electrode surfaces to improve the anti-interference ability and sensitivity are urgently needed for direct analysis of complex samples with high performance.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, there has been little research on the effects of the interaction of various ingredients in tea on the antioxidant capacity and the mechanism of their action, the traditional in vitro antioxidant detection method uses a UV-spectrophotometer to detect changes in the content of various color components, but this will be affected by the color and turbidity of the sample itself, so that the result is a large error, while electrochemical sensors have been widely used in food detection because of their high sensitivity, good selectivity, low cost, and fast analysis speed. 21–23 Therefore, the use of electrochemical technology to explore the synergistic effect of theanine on the antioxidant capacity of catechin can not only allow consumers to clear the mechanism of action to understand the benefits of drinking tea, but also promote the development of the food industry.…”
Section: Introductionmentioning
confidence: 99%